(3GdfcJ GddhPYjI Ydi TQM GdLRQjIs - (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdSfjcj GdeUQj GdTGaYqj, CHh jMji , J (B926 (3g` s
(3ChdgG (B:s
(3hHYO agPg MGTjI Ydi TQM SjOjRcQjG GdCfUGQj GdNRQLj GdTGaYj s
(3BNQgG (B:s
(3hbhd GdQhej GdMeO ddg eHJOC hNHQ GdLedI aj eMd JeJ GdMGTjI s
(3Vef eLehY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B275 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B292 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B188s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1799s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCRgQjI (B((3eLGejY (B213) s
Keywords: (3GdbQGAGJ hGdJLhjOs